Small Molecule Inhibitors Specifically Targeting the Type III Secretion System of Xanthomonas oryzae on Rice - Tao, Hui (Int J Mol Sci, 2019)
The initiative strategy for the development of novel anti-microbial agents usually uses the virulence factors of bacteria as a target, without affecting their growth and survival. The type III secretion system (T3SS), one of the essential virulence factors in most Gram-negative pathogenic bacteria because of its highly conserved construct, has been regarded as an effective target that developed new anti-microbial drugs. Xanthomonas oryzae pv. oryzae (Xoo) causes leaf blight diseases and is one of the most important pathogens on rice. To find potential anti-virulence agents against this pathogen, a number of natural compounds were screened for their effects on the T3SS of Xoo. Three of 34 compounds significantly inhibited the promoter activity of the harpin gene, hpa1, and were further checked for their impact on bacterial growth and on the hypersensitive response (HR) caused by Xoo on non-host tobacco plants. The results indicated that treatment of Xoo with CZ-1, CZ-4 and CZ-9 resulted in an obviously attenuated HR without affecting bacterial growth and survival. Moreover, quantitative reverse transcription-polymerase chain reaction (qRT-PCR) analysis showed that the expression of the Xoo T3SS was suppressed by treatment with the three inhibitors. The mRNA levels of representative genes in the hypersensitive response and pathogenicity (hrp) cluster, as well as the regulatory genes hrpG and hrpX, were reduced. Finally, the in vivo test demonstrated that the compounds could reduce the disease symptoms of Xoo on the rice cultivar (Oryza sativa) IR24.